The Study of Expanded Polytetrafluoroethylene New Material in Dural Repair. (14th March 2022) - Xu, Yong-Qiang; Gao, Wen-Bo; Xing, Meng-Yang; Gao, Yang; Zhang, Hai-Tao; Chen, Wei; Liu, Peng-Fei
Abstract : Dural defect is a common problem in neurosurgery, and the emergence of expanded polytetrafluoroethylene material provides an effective solution for the rehabilitation of artificial blood vessels, heart patches, and other fields. However, studies on the repair of expanded polytetrafluoroethylene in the dura have reported the occurrence of adverse events of cerebrospinal fluid leakage. Therefore, the task of improving expanded polytetrafluoroethylene materials cannot be delayed. In this study, a new composite dural repair material based on expanded polytetrafluoroethylene and polylactic acid-glycolic acid (expanded polytetrafluoroethylene/polylactic acid-glycolic acid) was designed and synthesized. The results of in vivo experiments confirmed that the material can fully meet the requirements of repairing the integrity of the dura mater, providing protection for the intracranial structure and rebuilding the extracellular matrix. More importantly, the new composite dural repair material can greatly reduce the incidence of cerebrospinal fluid leakage and inhibit inflammation. Therefore, the application data of this study on New Zealand rabbit species will lay an important foundation for the development of dural repair technology.